Steam caps in geothermal reservoirs can be monitored using seismic noise interferometry - Sánchez Sánchez-Pastor, Maria Del Pilar; id_orcid:0 000-0002-1163-5488; Wu, Sin-Mei; id_orcid:0 000-0001-8330-471X; Hokstad, Ketil; Kristjánsson, Bjarni; Drouin, Vincent; Ducrocq, Cécile; Gunnarsson, Gunnar; Rinaldi, Antonio Pio; id_orcid:0 000-0001-7052-8618; Wiemer, Stefan; et al. (Nature, 2023)
Harvesting geothermal energy often leads to a pressure drop in reservoirs, decreasing their profitability and promoting the formation of steam caps. While steam caps are valuable energy resources, they also alter the reservoir thermodynamics. Accurately measuring the steam fraction in reservoirs is essential for both operational and economic perspectives. However, steam content estimations are very limited both in space and time since current methods rely on direct measurements within production wells. Besides, these estimations normally present large uncertainties. Here, we present a pioneering method for indirectly sampling the steam content in the subsurface using the ever-present seismic background noise. We observe a consistent annual velocity drop in the Hengill geothermal field (Iceland) and establish a correlation between the velocity drop and steam buildup using in-situ borehole data. This application opens new avenues to track the evolution of any gas reservoir in the crust with a surface-based and cost-effective method. ISSN:2662-4435